Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.icesjms.2003.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of redfish (Sebastes marinus, S. mentella, and S. fasciatus) on the Flemish Cap (Northwest Atlantic)

Abstract: Age determination of redfish is difficult. In this paper, the ages of Sebastes mentella on the Flemish Cap are validated by following year classes from 1991 to 2000. The criteria used for S. mentella are consistent and coherent. The growth of different year classes is described and compared, and density-dependence is demonstrated to influence the growth rate of the strong 1990 year class, growth of that year class being the slowest of those followed. The slow rate of growth prevented that year class from matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
2
20
0
1
Order By: Relevance
“…Bomb radiocarbon is well established as an effective method of age validation for long-lived species, often with a precision of as little as 1-2 years (Kalish 1993;Campana 2001). Given that two previous radiochemical studies have confirmed the overall accuracy of C&B preparations and sections for determining the age of S. mentella and S. marinus in the Atlantic (albeit with low precision; Campana et al 1990;Stransky et al 2005a), and in light of another two studies that have confirmed the accuracy of these methods for ageing S. mentella to an age of 10 years (Mayo et al 1981;Saborido-Rey et al 2004), the bomb radiocarbon results in the present study were initially puzzling. The consistent offset of 9 years between the NWA reference chronology and the redfish core chronology indicates that either our growth increment counts were underaged by 9 years in every fish that we aged or the NWA surface marine chronology was inappropriate for use on Sebastes spp.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Bomb radiocarbon is well established as an effective method of age validation for long-lived species, often with a precision of as little as 1-2 years (Kalish 1993;Campana 2001). Given that two previous radiochemical studies have confirmed the overall accuracy of C&B preparations and sections for determining the age of S. mentella and S. marinus in the Atlantic (albeit with low precision; Campana et al 1990;Stransky et al 2005a), and in light of another two studies that have confirmed the accuracy of these methods for ageing S. mentella to an age of 10 years (Mayo et al 1981;Saborido-Rey et al 2004), the bomb radiocarbon results in the present study were initially puzzling. The consistent offset of 9 years between the NWA reference chronology and the redfish core chronology indicates that either our growth increment counts were underaged by 9 years in every fish that we aged or the NWA surface marine chronology was inappropriate for use on Sebastes spp.…”
Section: Discussionmentioning
confidence: 93%
“…Few other studies have attempted to compare the growth of these two Sebastes species, in part because of their problematic species identification. In comparing the growth and longevity of S. fasciatus, S. mentella and S. marinus on the Flemish Cap, Saborido-Rey et al (2004) commented on the difficulty of distinguishing between the first two species, but then neglected to state how they identified the species. They concluded that S. marinus grew fastest, S. mentella grew slowest and that longevities ranged from 32 to 34 years for S. mentella and S. fasciatus (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have described the biology and ecology of Flemish Cap fish species (Rodríguez-Marín et al, MS 1994;Rodríguez-Marín and De Cárdenas, MS 1997;Saborido-Rey and Junquera, 1999 a,b;Murua, MS 2000;Saborido-Rey, MS 2001;Alpoim et al, MS 2002). Most previous works concerned single species and speciesspecific spatial distributions, population dynamics or biology.…”
Section: Introductionmentioning
confidence: 99%
“…Between-sex differences in growth were tested using the Chow test (Chow, 1960;Saborido-Rey et al, 2004).…”
Section: Age Determination and Growth Calculationmentioning
confidence: 99%